WERNER SYNDROME: A NEW CASE REPORT - Faida Ajili; Wafa Garbouj; Najeh Boussetta; Janet Laabidi; Nadia Ben Abdelhafidh; Bassem Louzir; Salah Othmani (Our Dermatology Online, 2013)
"Werner's syndrome" or premature aging syndrome is a rare autosomal recessive genetic disease. It is responsible of several complications related to age, including atherosclerosis and association with cancer. We report the case of a 36 year-old-patient, admitted to department of Internal Medicine of the military hospital of Tunis for suspicion of systemic sclerosis. The patient had all the major signs of Werner syndrome (bilateral cataract, sclerotic skin, "bird face", baldness, small size, parental consanguinity) and 4 minor signs (type 2 diabetes, hypogonadism, squeaky voice, and flat feet). She has also a brother with the same morphotype died at the age of 32 by a myocardial infarction. The current follow-up time is 9 years..